Polymer containing fluorenyl structure, preparation method of polymer, hard mask composition and application of hard mask composition
By designing a hard mask composition containing fluorenyl structure polymer, the shortcomings of the hard mask in terms of etch resistance and solubility are solved, and efficient pattern transfer and good thermal stability of the hard mask are achieved.
Patent Information
- Application Number
- CN202510575591.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-06
- Publication Date
- 2025-08-08
AI Technical Summary
Existing hard mask compositions cannot have both good etch resistance and dissolution properties, resulting in pattern distortion or failure during the transfer of the photolithography of the hard mask.
A fluorenyl-containing structure-containing polymer is designed and synthesized, and a hard mask composition is prepared, including fluorenyl-containing structure-containing polymer, organic solvent, crosslinking agent, catalyst and surfactant, and a polymer with a specific structure is formed through a condensation reaction, which imparts good solubility, etch resistance and thermal stability to the hard mask.
The hard mask exhibits good planarization and gap filling characteristics, maintaining good thermal stability and high etch resistance, ensuring fidelity transfer of the lithographic pattern.
Smart Images

Figure CN120441788A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of photolithography, and in particular relates to a fluorene-containing structural polymer, a preparation method thereof, and a hard mask composition and application thereof. Background Art
[0002] In recent years, in some lithographic processes (photolithography processes), there is a tendency to ensure the integrity of the pattern and prevent the collapse of fine photolithographic patterns by using a thinner layer of resist material. However, when the substrate to be etched (the target material layer) is very thick, the etching resistance of the thin resist material layer is insufficient, resulting in the inability to effectively transfer the desired pattern to the lower layer of the resist material. Therefore, it is necessary to form a hard mask as an intermediate layer between the substrate and the resist material layer, the role of which is to receive the pattern from the resist material layer and transfer the pattern to the substrate. Since the hard mask transfers the fine pattern on the photoresist to the material layer through a selective etching process, the hard mask is required to have characteristics such as heat resistance and etching resistance, so that it has a higher tolerance during various etching processes to better complete the pattern transfer process. Currently, much research has been conducted on improving the etch resistance of hardmasks. This is often achieved by using hardmask compositions containing high-carbon polymers. However, these materials have poor solubility and thermal stability, adversely affecting the planarization and gapfill characteristics of the hardmask and potentially leading to pattern distortion or failure during the transfer of the photolithographic pattern from the hardmask. Therefore, there is an urgent need to develop a hardmask composition that combines excellent etch resistance, solubility, and thermal stability. Summary of the Invention
[0003] The purpose of the present invention is to address the problem that existing hard mask compositions cannot simultaneously have good etching resistance, solubility and thermal stability, which leads to pattern distortion or failure during the hard mask transfer photolithography pattern. The present invention provides a fluorene-based structure polymer and its preparation method, a hard mask composition and application. The hard mask composition containing the fluorene-based structure polymer has good solubility, etching resistance and thermal stability.
[0004] In a first aspect, the present invention provides a fluorene-containing polymer. The fluorene-containing polymer has a structure as shown in formula (1):
[0005]
[0006] In formula (1), R1 and R2 are each independently a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, n is an integer from 1 to 500, and R3 has a structure as shown in formula (2) or formula (3), wherein, represents the bond connecting R2 and other structural units, R4 is a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or a monovalent aromatic group having 6 to 20 carbon atoms, and R5 is a divalent aromatic group having 6 to 20 carbon atoms.
[0007] In a preferred embodiment, the R3 has at least one of the following structures:
[0008]
[0009] In a preferred embodiment, the weight average molecular weight of the fluorene-containing structure polymer is 5000 to 15000 Da, and the PDI is 1.5 to 2.5.
[0010] In a second aspect, the present invention provides a method for preparing the aforementioned fluorene-containing structure polymer. The method comprises condensing a fluorene-containing compound having the structure represented by formula (4) with an aldehyde compound and / or a diol compound, and obtaining a fluorene-containing structure polymer having the structure represented by formula (1) as the resulting reaction product.
[0011]
[0012] In formula (4), R1 and R2 are each independently a hydrogen atom or an alkyl group having 1 to 6 carbon atoms.
[0013] In a preferred embodiment, the aldehyde compound is an aliphatic aldehyde and / or an aromatic aldehyde.
[0014] In a preferred embodiment, the fatty aldehyde is selected from at least one of formaldehyde, paraformaldehyde, acetaldehyde, propionaldehyde and butyraldehyde.
[0015] In a preferred embodiment, the aromatic aldehyde is at least one selected from benzaldehyde, naphthalene formaldehyde, anthracene formaldehyde, pyrene formaldehyde, and p-hydroxybenzaldehyde.
[0016] In a preferred embodiment, the diol compound is an aromatic diol compound and / or an aromatic diol derivative.
[0017] In a preferred embodiment, the aromatic diol compound is selected from at least one of dihydroxymethylbenzene, dihydroxymethylbiphenyl, dihydroxymethylnaphthalene and dihydroxymethylanthracene.
[0018] In a preferred embodiment, the aromatic diol derivative is at least one selected from di(methoxymethyl)benzene, di(methoxymethyl)biphenyl, di(methoxymethyl)naphthalene and di(methoxymethyl)anthracene.
[0019] In a preferred embodiment, the molar ratio of the fluorenyl-containing compound to the aldehyde compound and / or diol compound is 1:(1-2).
[0020] In a preferred embodiment, the polycondensation reaction is carried out at a temperature of 50 to 200° C. and for a time of 1 to 48 hours.
[0021] In a preferred embodiment, the polycondensation reaction is carried out in the presence of an acidic catalyst and / or an organic solvent I.
[0022] In a third aspect, the present invention provides a hard mask composition comprising the above-mentioned fluorene-containing structure polymer, organic solvent II, and optionally a cross-linking agent, a catalyst, and a surfactant.
[0023] In a preferred embodiment, based on the total mass of the hard mask composition, the content of the fluorene-containing structural polymer is 5 to 20 wt%, the content of the organic solvent II is 75 to 90 wt%, the content of the cross-linking agent is 0.3 to 2 wt%, the content of the catalyst is 0.002 to 0.1 wt%, and the content of the surfactant is 0.02 to 3 wt%.
[0024] In a fourth aspect, the present invention provides application of the hard mask composition in photolithography technology.
[0025] Beneficial effects: The present invention designs and synthesizes a fluorene-containing structural polymer with a specific structure, thereby giving the hard mask composition containing the polymer good solubility, etching resistance and thermal stability, so that the formed hard mask has good planarization characteristics and gap filling characteristics, and the hard mask can maintain good thermal stability and exhibit high etching resistance during the transfer of the photolithographic pattern, ensuring that the photolithographic pattern is faithfully and effectively transferred to the target base material layer. DETAILED DESCRIPTION
[0026] The fluorene-containing polymer provided by the present invention has a structure as shown in formula (1):
[0027]
[0028] In formula (1), R1 and R2 are each independently a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, and n is an integer from 1 to 500. R3 has a structure as shown in formula (2) or formula (3), wherein: represents the bond connecting R2 and other structural units, R4 is a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or a monovalent aromatic group having 6 to 20 carbon atoms, and R5 is a divalent aromatic group having 6 to 20 carbon atoms. Specific examples of the alkyl group having 1 to 6 carbon atoms include, but are not limited to, one of: methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, 1-methylbutyl, 2-methylbutyl, 3-methylbutyl, 1,1-dimethylpropyl, 2,2-dimethylpropyl, 1,2-dimethylpropyl, 1-ethylpropyl, n-hexyl, 1-methylpentyl, 2-methylpentyl, 3-methylpentyl, 4-methylpentyl, 1,1-dimethylbutyl, 2,2-dimethylbutyl, 3,3-dimethylbutyl, 1,2-dimethylbutyl, 1,3-dimethylbutyl, 2,3-dimethylbutyl, 1-ethylbutyl, 2-ethylbutyl, and 3-ethylbutyl. Specific examples of the monovalent aromatic group having 6 to 20 carbon atoms include, but are not limited to, one of: phenyl, naphthyl, anthracenyl, phenanthrenyl, pyrenyl, benzopyrenyl, and biphenyl. Specific examples of the divalent aromatic group having 6 to 20 carbon atoms include, but are not limited to, one of a divalent phenyl group, a divalent naphthyl group, a divalent anthracenyl group, a divalent phenanthrenyl group, a divalent pyrene group, a divalent benzopyrene group, and a divalent biphenyl group.
[0029] In the present invention, the R3 preferably has at least one of the following structures:
[0030]
[0031] In the present invention, the weight average molecular weight (Mw) of the fluorene-containing polymer is preferably 5,000 to 15,000 Da, such as 5,000 Da, 6,000 Da, 7,000 Da, 8,000 Da, 9,000 Da, 10,000 Da, 12,000 Da, 15,000 Da, or any value therebetween. The PDI of the fluorene-containing polymer is preferably 1.5 to 2.5, such as 1.5, 1.7, 1.9, 2.0, 2.2, 2.5, or any value therebetween.
[0032] The preparation method of the fluorene-containing structure polymer provided by the present invention comprises the following steps: subjecting a fluorene-containing compound represented by formula (4) to a condensation reaction with an aldehyde compound and / or a diol compound; the resulting reaction product is a fluorene-containing structure polymer represented by formula (1).
[0033]
[0034] In formula (4), R1 and R2 are each independently a hydrogen atom or an alkyl group having 1 to 6 carbon atoms. Specific examples of the alkyl group having 1 to 6 carbon atoms are the same as those described above and will not be repeated here.
[0035] In the present invention, the aldehyde compound is a compound capable of undergoing a condensation reaction with a fluorenyl-containing compound to provide an R3 group for the fluorenyl-containing polymer. The compound may be an aliphatic aldehyde and / or an aromatic aldehyde. Specific examples of the aliphatic aldehyde include, but are not limited to, at least one of formaldehyde, paraformaldehyde, acetaldehyde, propionaldehyde, and butyraldehyde. Specific examples of the aromatic aldehyde include, but are not limited to, at least one of benzaldehyde, naphthalene formaldehyde, anthracene formaldehyde, pyrene formaldehyde, and p-hydroxybenzaldehyde.
[0036] In the present invention, the diol compound is a type of compound that can undergo a polymerization reaction with a fluorene-containing compound to provide an R3 group for a fluorene-containing structural polymer, and can be an aromatic diol compound and / or an aromatic diol derivative. Specific examples of the aromatic diol compound include, but are not limited to, at least one of dihydroxymethylbenzene, dihydroxymethylbiphenyl, dihydroxymethylnaphthalene, and dihydroxymethylanthracene. The aromatic diol derivative refers to a compound in which the hydrogen atoms on the two alcoholic hydroxyl groups in the aromatic diol compound are replaced by an alkyl group having 1 to 2 carbon atoms, and specific examples thereof include, but are not limited to, at least one of di(methoxymethyl)benzene, di(methoxymethyl)biphenyl, di(methoxymethyl)naphthalene, and di(methoxymethyl)anthracene.
[0037] In the present invention, the molar ratio of the fluorenyl-containing compound to the aldehyde compound and / or diol compound is preferably 1:(1-2), such as 1:1, 1:1.2, 1:1.5, 1:1.8, 1:2 or any value therebetween.
[0038] In the present invention, the temperature of the polycondensation reaction is preferably 50 to 200° C., such as 50° C., 80° C., 100° C., 120° C., 150° C., 180° C., 200° C., or any value therebetween. The time of the polycondensation reaction is 1 to 48 hours, such as 1 hour, 6 hours, 12 hours, 18 hours, 24 hours, 30 hours, 36 hours, 42 hours, 48 hours, or any value therebetween.
[0039] In the present invention, the polycondensation reaction is preferably carried out in the presence of an acidic catalyst, which is more conducive to promoting the polycondensation reaction. The acidic catalyst can be an organic acid and / or an inorganic acid. Specific examples of the inorganic acid include, but are not limited to, at least one of sulfuric acid, phosphoric acid, perchloric acid, nitric acid, and hydrochloric acid. Specific examples of the organic acid include, but are not limited to, at least one of p-toluenesulfonic acid, formic acid, oxalic acid, and salicylic acid.
[0040] In the present invention, the polycondensation reaction is preferably carried out in the presence of an organic solvent I, as long as it is a type of solvent that does not adversely affect the polycondensation reaction. Specific examples include, but are not limited to, at least one of tetrahydrofuran, propylene glycol monomethyl ether, propylene glycol dimethyl ether, propylene glycol monoethyl ether and propylene glycol monomethyl ether acetate.
[0041] The hard mask composition provided by the present invention contains the above-mentioned fluorene-containing structural polymer, organic solvent II, and optional crosslinking agent, catalyst, and surfactant.
[0042] In the present invention, based on the total mass of the hard mask composition, the content of the fluorene group-containing polymer is preferably 5 to 20 wt%, such as 5 wt%, 8 wt%, 10 wt%, 12 wt%, 15 wt%, 18 wt%, 20 wt% or any value therebetween; the content of the organic solvent II is preferably 75 to 90 wt%, such as 75 wt%, 78 wt%, 80 wt%, 82 wt%, 85 wt%, 88 wt%, 90 wt% or any value therebetween; the content of the cross-linking agent is preferably 0.3 to 2 wt%, such as 0.3 wt%, 0.5 wt%, 0.8 wt%, 1 wt%, 1. % , 5wt%, 2wt% or any value therebetween; the content of the catalyst is preferably 0.002-0.1wt%, such as 0.002wt%, 0.005wt%, 0.008wt%, 0.01wt%, 0.02wt%, 0.05wt%, 0.08wt%, 0.1wt% or any value therebetween; the content of the surfactant is preferably 0.02-3wt%, such as 0.02wt%, 0.05wt%, 0.08wt%, 0.1wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt% or any value therebetween.
[0043] In the present invention, the organic solvent II can be a conventional choice for preparing a hard mask composition in the prior art, and specific examples thereof include but are not limited to at least one of propylene glycol monomethyl ether acetate (PGMEA), propylene glycol monomethyl ether (PGME), cyclohexanone and ethyl lactate.
[0044] In the present invention, the crosslinking agent may be a conventional choice for preparing a hard mask composition in the prior art, and specific examples thereof include but are not limited to at least one of amino resins, glycoluril compounds, epoxy compounds, melamine, and melamine derivatives.
[0045] In the present invention, the catalyst may be a conventional choice for preparing a hard mask composition in the prior art, and specific examples thereof include but are not limited to at least one of p-toluenesulfonic acid, trifluoromethanesulfonic acid, pyridinium-p-toluenesulfonate, salicylic acid, camphorsulfonic acid, and benzene disulfonic acid.
[0046] In the present invention, the surfactant may be a conventional choice for preparing a hard mask composition in the prior art, and specific examples thereof include, but are not limited to, polyoxyethylene alkyl ethers such as polyoxyethylene lauryl ether, polyoxyethylene stearyl ether, polyoxyethylene cetyl ether, and polyoxyethylene glycerol ether; polyoxyethylene alkyl aryl ethers such as polyoxyethylene octylphenyl ether and polyoxyethylene nonylphenyl ether; sorbitan fatty acid esters such as sorbitan monolaurate, sorbitan monopalmitate, sorbitan monostearate, sorbitan monooleate, sorbitan trioleate, and sorbitan tristearate; and at least one of polyoxyethylene sorbitan fatty acid esters such as polyoxyethylene-sorbitan monolaurate, polyoxyethylene-sorbitan monopalmitate, polyoxyethylene-sorbitan monostearate, polyoxyethylene-sorbitan trioleate, and polyoxyethylene-sorbitan tristearate.
[0047] The present invention provides an application of the hard mask composition in photolithography, and more specifically, provides an application of the hard mask composition in a pattern forming method. The pattern forming method may include the following steps: forming a material layer on a substrate; applying the hard mask composition on the material layer and heat treating the hard mask; forming a thin silicon-containing layer on the hard mask; forming a photoresist layer on the silicon-containing layer; exposing and developing the photoresist layer to form a photoresist pattern; removing the silicon-containing layer and the hard mask using the photoresist pattern as a mask to expose a portion of the material layer; and etching the exposed portion of the material layer to obtain a pattern in the material layer.
[0048] In the present invention, the substrate can be any one of a silicon wafer substrate, a glass substrate, and a polymer substrate. The material layer is the material to be ultimately patterned, and can be any one of a metal layer such as an aluminum layer or a copper layer, a semiconductor layer such as a silicon layer, or an insulating layer such as silicon dioxide or silicon nitride.
[0049] In the present invention, the hard mask can be formed as follows: spin-coating the hard mask composition in solution on the material layer, and heat-treating it at 250-400° C. for 1-5 minutes to obtain a hard mask with a thickness of 50-500 nm.
[0050] In the present invention, the silicon-containing thin layer can be formed from any one of silicon nitride, silicon oxide, and silicon oxynitride. The photoresist layer can be formed from any one of ArF, KrF, and EUV photoresists. The exposure light source for the photoresist layer preferably corresponds to the type of photoresist and can be selected from any one of ArF, KrF, and EUV.
[0051] In the present invention, the methods and condition parameters of the material layer, silicon thin layer, photoresist layer, exposure and development of the photoresist layer, and etching treatment can be adaptively adjusted according to existing pattern forming methods.
[0052] In addition, the terms "I" and "II" are only for the purpose of convenience of description and should not be understood as special limitations on the type and / or amount of technical features.
[0053] The present invention will be described in detail below through specific examples. The examples of the embodiments are intended to explain the present invention and are not to be construed as limiting the present invention. Where specific techniques or conditions are not specified in the examples, the techniques or conditions described in the literature in this field or the product specifications are used. Where the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be obtained commercially.
[0054] Synthesis Example 1 Synthesis of Fluorene-containing Compound 1
[0055] To a 100mL flask equipped with a mechanical stirrer, thermometer, and condenser, 10g of 2,7-bis(diphenylamino)-9-fluorenone, 20g of phenol, and 15g of toluene were added, followed by stirring and placing in a water bath. 1.5g of concentrated sulfuric acid was added, and the reaction temperature was controlled at 20°C for 2 hours. The temperature was then raised to 30°C and the reaction continued for 1 hour. Once the system had completely transformed into a pure white slurry, 30g of toluene was added, the temperature was cooled to room temperature, and the mixture was filtered. The filter cake was washed with a small amount of toluene, filtered, and dried to yield 11g of a pure white solid, the fluorenyl-containing compound 1. Its synthesis process and specific structure are shown below.
[0056]
[0057] NMR verification confirmed that the fluorenyl-containing compound 1 indeed has the structure shown in formula (4-1). NMR test results: 1H-NMR (300 MHz, DMSO) δ (ppm) 9.06 (s, 2H), 7.33 (s, 2H), 7.86 (d, 2H), 6.67 (d, 4H), 7.16 (d, 2H), 7.08 (d, 8H), 7.01 (d, 4H), 7.24 (q, 8H), 7.00 (q, 4H).
[0058] Synthesis Example 2 Synthesis of Fluorene-containing Compound 2
[0059] To a 100mL flask equipped with a mechanical stirrer, thermometer, and condenser, 10g of 2,7-bis(diphenylamino)-9-fluorenone, 20g of o-methylphenol, and 15g of toluene were added, sequentially. The mixture was stirred and placed in a water bath. 1.5g of concentrated sulfuric acid was added. The reaction temperature was controlled at 20°C for 2 hours, then raised to 30°C and continued for 1 hour. Once the system had completely transformed into a pure white slurry, 30g of toluene was added, the temperature was cooled to room temperature, and the mixture was filtered. The filter cake was washed with a small amount of toluene, filtered, and dried to yield 11g of a pure white solid, the fluorenyl-containing compound 2. Its synthesis process and specific structure are shown below.
[0060]
[0061] After nuclear magnetic resonance verification, the fluorenyl-containing compound 2 does have the structure shown in formula (4-2). Nuclear magnetic resonance detection results: 1H-NMR (300MHz, DMSO) δ (ppm) 9.68 (s, 2H), 7.33 (s, 2H), 7.86 (d, 2H), 6.75 (d, 2H), 7.16 (d, 2H), 7.08 (d, 8H), 6.92 (d, 2H), 6.91 (d, 2H), 7.24 (q, 8H), 7.00 (q, 4H), 2.15 (s, 6H).
[0062] Synthesis Example 3 Synthesis of Fluorene-containing Polymer 1
[0063] In a three-necked flask equipped with a mechanical stirrer and a condenser, 68.48 g (0.1 mol) of the fluorene-containing compound 1, 0.85 g of p-toluenesulfonic acid, and 250 mL of propylene glycol monomethyl ether were added and stirred until completely dissolved. The reactor temperature was raised to 120°C, and 16.62 g (0.1 mol) of 1,4-bis(methoxymethyl)benzene was added dropwise to the solution. The resulting mixture was reacted at 120°C for 12 hours, and then 1.27 g of triethanolamine was added as a neutralizer to quench the reaction. After the reaction was completed, the reaction solution was cooled and poured into methanol to remove unreacted monomer compounds and low-molecular-weight polymers. The mixture was filtered, and the filter cake was further washed with methanol twice. After drying in a vacuum oven at 50°C for 10 hours, the fluorene-containing polymer 1 shown in Chemical Formula 1-1 was obtained. After testing, the weight average molecular weight Mw of the fluorene-containing structure polymer 1 was 5800 Da, and the PDI was 2.1.
[0064]
[0065] Synthesis Example 4 Synthesis of Fluorene-containing Polymer 2
[0066] Fluorene-containing polymer 2 was prepared according to the method of Synthesis Example 3, except that an equal amount of formaldehyde was used instead of 1,4-bis(methoxymethyl)benzene. All other conditions were the same as those of Synthesis Example 3, thereby obtaining fluorene-containing polymer 2 represented by Chemical Formula 1-2. Testing revealed that the weight-average molecular weight (Mw) of fluorene-containing polymer 2 was 8450 Da, and the PDI was 2.5.
[0067]
[0068] Synthesis Example 5 Synthesis of Fluorene-containing Polymer 3
[0069] Fluorene-containing polymer 3 was prepared according to the method of Synthesis Example 3, except that 9,10-dimethoxymethylanthracene was used instead of 1,4-bis(methoxymethyl)benzene in equal moles. All other conditions were the same as those of Synthesis Example 3, thereby obtaining fluorene-containing polymer 3 represented by Chemical Formula 1-3. Testing revealed that the weight-average molecular weight (Mw) of fluorene-containing polymer 3 was 10,200 Da, and the PDI was 1.8.
[0070]
[0071] Synthesis Example 6 Synthesis of Fluorene-containing Polymer 4
[0072] Fluorene-containing polymer 4 was prepared according to the method of Synthesis Example 3, except that an equal amount of naphthalene formaldehyde was used instead of 1,4-bis(methoxymethyl)benzene. All other conditions were the same as those of Synthesis Example 3, thereby obtaining fluorene-containing polymer 4 represented by Chemical Formula 1-4. Testing revealed that the weight-average molecular weight (Mw) of fluorene-containing polymer 4 was 8600 Da, and the PDI was 2.0.
[0073]
[0074] Synthesis Example 7 Synthesis of Fluorene-containing Polymer 5
[0075] Fluorene-containing polymer 5 was prepared according to the method of Synthesis Example 3, except that 1,4-bis(methoxymethyl)benzene was replaced with an equal molar amount of 2,6-dihydroxynaphthalene. All other conditions were the same as those of Synthesis Example 3, thereby obtaining fluorene-containing polymer 5 represented by Chemical Formula 1-5. Testing revealed that the weight-average molecular weight (Mw) of fluorene-containing polymer 5 was 12,800 Da, and the PDI was 2.2.
[0076]
[0077] Synthesis Example 8 Synthesis of Fluorene-containing Polymer 6
[0078] Fluorene-containing polymer 6 was prepared according to the method of Synthesis Example 3, except that an equal molar amount of fluorene-containing compound 2 was used instead of fluorene-containing compound 1. All other conditions were the same as those of Synthesis Example 3, thereby obtaining fluorene-containing polymer 6 represented by Chemical Formula 1-6. Testing revealed that the weight-average molecular weight (Mw) of fluorene-containing polymer 6 was 10,700 Da, and the PDI was 1.7.
[0079]
[0080] Comparative Synthesis Example 1 Synthesis of Fluorene-containing Polymer 7
[0081] Fluorene-containing polymer 7 was prepared according to the method of Synthesis Example 3, except that the same molar amount of 9,9-bis(4-hydroxyphenyl)fluorene was used instead of fluorene-containing compound 1. The remaining conditions were the same as those of Synthesis Example 3, thereby preparing fluorene-containing polymer 7 represented by Chemical Formula 1-7. Testing showed that the weight-average molecular weight (Mw) of fluorene-containing polymer 7 was 11,755 Da, and the PDI was 2.4.
[0082]
[0083] Preparation of Hard Mask Compositions of Examples 1 to 8 and Comparative Example 1
[0084] The fluorene-containing polymer obtained in the above synthesis example was mixed with an organic solvent, a crosslinker, a catalyst, and a surfactant according to the ratios shown in Table 1 until the components were dissolved and mixed uniformly. The resulting mixture was filtered to obtain a hardmask composition. The organic solvent was propylene glycol monomethyl ether acetate (PGMEA), the catalyst was p-toluenesulfonic acid, the crosslinker was tetramethoxymethyl glycoluril, and the surfactant was polyoxyethylene lauryl ether.
[0085] Table 1
[0086]
[0087] Test Case
[0088] (1) Planarization and Gap Fill Characteristics Test: The hard mask compositions obtained in Examples 1 to 8 and Comparative Example 1 were spin-coated on a patterned silicon wafer and treated on a hot plate at 400°C for 180 seconds to form a hard mask film. The cross-section of the formed hard mask was observed using a field emission scanning electron microscope to determine whether there were gaps to evaluate the gap fill characteristics. The planarization characteristics were then determined by the difference between the thickest portion (line portion) and the thinnest portion (space portion) of the hard mask. A difference of less than 5 nm was considered "very good" for the planarization characteristics, between 5 and 10 nm was considered "good", and greater than 10 nm was considered "poor". The results are shown in Table 2.
[0089] (2) Etching Resistance Test: The hard mask compositions obtained in Examples 1 to 8 and Comparative Example 1 were each coated onto a silicon wafer using a spin coater and treated on a hot plate at 400°C for 120 seconds to form a hard mask. The film thickness was measured using a film thickness meter manufactured by K-MAC. The hard mask was then etched using a CHF3 / CF4 mixed gas under the following conditions: a chamber pressure of 40 Pa, an RF power of 1500 W, a CHF3 flow rate of 30 mL / min, and a CF4 flow rate of 30 mL / min. After etching, the film thickness was measured again, and the etch rate was characterized using the result of Formula 1. The results are shown in Table 1.
[0090] Calculation formula 1: Etching rate = (initial thickness of the resist underlayer film - thickness of the resist underlayer film after etching) / etching time.
[0091] (3) Heat Resistance Test: The hard mask compositions obtained in Examples 1 to 8 and Comparative Example 1 were each coated onto a silicon wafer using a spin coater and treated on a hot plate at 250°C for 60 seconds to form a hard mask film. The thickness at this point was measured using a K-MAC film thickness gauge. The film was then baked again at 400°C for 2 minutes, and its thickness was measured again. The film thickness reduction rate of the hard mask film was calculated according to Formula 2 to illustrate its heat resistance. The resulting structure is shown in Table 2.
[0092] Calculation formula 2: (thickness of the film after baking at 250° C.−thickness of the film after baking at 400° C.) / thickness of the film after baking at 250° C.×100(%).
[0093] Table 2
[0094]
[0095] It can be seen from the results in Table 1 that, compared with the comparative example, the hard mask formed by the hard mask composition provided by the embodiment of the present invention has excellent planarization characteristics and gap filling characteristics, and also exhibits a lower CHF3 / CF4 etching rate and film thickness reduction rate, and has good etching resistance and thermal stability.
[0096] Although the embodiments of the present invention have been shown and described above, it will be understood that the above embodiments are illustrative and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and purpose of the present invention.
Claims
1. A fluorene-containing polymer, characterized in that: The fluorene-containing polymer has a structure as shown in formula (1): In formula (1), R1 and R2 are each independently a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, n is an integer from 1 to 500, and R3 has a structure as shown in formula (2) or formula (3), wherein, represents the bond connecting R2 and other structural units, R4 is a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or a monovalent aromatic group having 6 to 20 carbon atoms, and R5 is a divalent aromatic group having 6 to 20 carbon atoms.
2. The fluorene group-containing structure polymer according to claim 1, characterized in that The R3 has at least one of the following structures:
3. The fluorene group-containing structure polymer according to claim 1, characterized in that: The weight average molecular weight of the fluorene-containing structure polymer is 5000-15000 Da, and the PDI is 1.5-2.
5.
4. The method for preparing a fluorene group-containing polymer according to any one of claims 1 to 3, wherein: The preparation method comprises the steps of condensing a fluorene-containing compound represented by formula (4) with an aldehyde compound and / or a diol compound, and obtaining a reaction product which is a fluorene-containing structure polymer represented by formula (1); In formula (4), R1 and R2 are each independently a hydrogen atom or an alkyl group having 1 to 6 carbon atoms.
5. The method for preparing a fluorene-containing structure polymer according to claim 4, wherein: The aldehyde compound is an aliphatic aldehyde and / or an aromatic aldehyde; Preferably, the fatty aldehyde is selected from at least one of formaldehyde, paraformaldehyde, acetaldehyde, propionaldehyde and butyraldehyde; Preferably, the aromatic aldehyde is at least one selected from benzaldehyde, naphthalene formaldehyde, anthracene formaldehyde, pyrene formaldehyde, and p-hydroxybenzaldehyde; Preferably, the diol compound is an aromatic diol compound and / or an aromatic diol derivative; Preferably, the aromatic diol compound is selected from at least one of dihydroxymethylbenzene, dihydroxymethylbiphenyl, dihydroxymethylnaphthalene and dihydroxymethylanthracene; Preferably, the aromatic diol derivative is at least one selected from di(methoxymethyl)benzene, di(methoxymethyl)biphenyl, di(methoxymethyl)naphthalene and di(methoxymethyl)anthracene.
6. The method for preparing a fluorene-containing structure polymer according to claim 4, wherein: The molar ratio of the fluorenyl-containing compound to the aldehyde compound and / or diol compound is 1:(1-2); Preferably, the temperature of the polycondensation reaction is 50 to 200° C., and the time is 1 to 48 hours.
7. The method for preparing a fluorene-containing structure polymer according to claim 4, wherein: The polycondensation reaction is carried out in the presence of an acidic catalyst and / or an organic solvent I.
8. A hard mask composition, characterized in that The hard mask composition contains the fluorene group-containing structure polymer according to any one of claims 1 to 3, an organic solvent II, and optionally a crosslinking agent, a catalyst, and a surfactant.
9. The hard mask composition according to claim 8, wherein Based on the total mass of the hard mask composition, the content of the fluorene-containing structural polymer is 5-20wt%, the content of the organic solvent II is 75-90wt%, the content of the crosslinking agent is 0.3-2wt%, the content of the catalyst is 0.002-0.1wt%, and the content of the surfactant is 0.02-3wt%.
10. Use of the hard mask composition according to claim 8 or 9 in photolithography technology.